Therapeutic effects of amla in medicine and dentistry: A review - Harpreet Singh Grover; Himanshu Deswal; Yogender Singh; Amit Bhardwaj (Wolters Kluwer Medknow Publications, 2015)
Emblica officinalis (Amla) is widely used in the Indian system of medicine and believed to increase defense against diseases. Amla is called amalaki in Sanskrit. It is one of the oldest oriental medicines mentioned in Ayurveda as potential remedy for assorted ailments. A wide range of phytochemical components present in amla including alkaloids, tannins, and flavonoids have been shown to procure useful biological activities. It is an ingredient of many Ayurvedic medicines and tonics as it removes excessive salivation and internal body heat. Research has been done with amla evaluating its role as an antioxidant. Amla is useful in ulcer prevention, for diabetic patients, and for memory effects. Amla Tonic has a hematinic and lipalytic function useful in scurvy, prevents indigestion, and controls acidity as well as it is a natural source of anti-aging.